2016
DOI: 10.1111/cei.12811
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vasostatin-1-specific CD8+ T cells in non-obese diabetic mice that contribute to diabetes pathogenesis

Abstract: SummaryChromogranin A (ChgA) is an antigenic target of pathogenic CD41 T cells in a non-obese diabetic (NOD) mouse model of type 1 diabetes (T1D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…HLA-A3 1 patients with new-onset T1D (n 5 9; median age 26 years [range [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]; median disease duration 1.4 weeks [range 0.3-32]) and age/sex-matched healthy donors (Supplementary Table 1) gave written informed consent under ethics approval DC-2015-2536 Ile-de-France I. HLA-A3 (A*03:01) typing was performed with AmbiSolv primers (Dynal/Thermo Fisher Scientific). Blood was drawn into 9-mL sodium heparin tubes and peripheral blood mononuclear cells (PBMCs) isolated and frozen as described (3,28).…”
Section: Study Participants and Blood Processingmentioning
confidence: 99%
“…HLA-A3 1 patients with new-onset T1D (n 5 9; median age 26 years [range [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]; median disease duration 1.4 weeks [range 0.3-32]) and age/sex-matched healthy donors (Supplementary Table 1) gave written informed consent under ethics approval DC-2015-2536 Ile-de-France I. HLA-A3 (A*03:01) typing was performed with AmbiSolv primers (Dynal/Thermo Fisher Scientific). Blood was drawn into 9-mL sodium heparin tubes and peripheral blood mononuclear cells (PBMCs) isolated and frozen as described (3,28).…”
Section: Study Participants and Blood Processingmentioning
confidence: 99%
“…The protein encoded by Chga , chromogranin A, is a member of the chromogranin/secretogranin family of neuroendocrine secretory proteins and a precursor to three biologically-active peptides, vasostatin, pancreastatin and parastatin. The first inhibits angiogenesis and suppresses tumor growth, the second strongly inhibits glucose-induced insulin release from the pancreas, and the third inhibits parathyroid cell secretion [3840]. The extent of down-regulation of the other genes shown on Table 2 were greater than 2 −4.37 -fold change.…”
Section: Resultsmentioning
confidence: 99%
“…CgA helps regulate secretion in granules and produces several degradation products after secretion. Some of the products obtained after CgA degradation alter hormonal functions in autocrine and paracrine ways [9,18].Recent studies [13,15,16,17,19,20,23] have shown that CgA and some of its breakdown products, namely (pancreastatin, catestatin, vasostatin 1, WE-14) play an important role in the pathogenesis of various forms of diabetes [4,6,14,18,24], but the exact mechanisms of their action are still unclear. Several studies [12,17,20] have reported higher levels of pancreastatin and WE-14 in patients with type 1 and type 2 diabetes [12].According to a number of authors [1,11,13,15,18], pancreastatin, catestatin, and vasostatin play an important role in metabolic syndromes, namely obesity, diabetes, and others.…”
mentioning
confidence: 99%
“…Recent studies [13,15,16,17,19,20,23] have shown that CgA and some of its breakdown products, namely (pancreastatin, catestatin, vasostatin 1, WE-14) play an important role in the pathogenesis of various forms of diabetes [4,6,14,18,24], but the exact mechanisms of their action are still unclear. Several studies [12,17,20] have reported higher levels of pancreastatin and WE-14 in patients with type 1 and type 2 diabetes [12].…”
mentioning
confidence: 99%